Effects of swimming exercise and RLN2 induction on relaxin levels, MMP-13, TGFβ expression in the pubic cartilage of pregnant rats - Ika Oktaviani; Titin Andri Wihastuti; Bambang Rahardjo; Endang Sri Wahyuni; Bilqisthi Ari Putra (Journal of Pharmacy & Pharmacognosy Research, 2022)
Context: Swimming exercises can be used as an intervention to maintain the stability of the synthesis of the pubic symphysis cartilage.